A Prototype Fabrication of Sensitive Porous Silicon NOx (x=1,2) Gas Sensor - Nyoman Sudiana; Muhammad Anas; Muhammad Jahiding Hafid (Jurnal ILMU DASAR, 2010)
A prototype of (porous silicon (PS) based) NO(x=1.2) gas sensor based on porous silicon (PS) (operated at room temperature) has been fabricated. The sensor could be operated at room temperature. The (PS) basic material for the material sensor ( i.e. PS) was fabricated in the previous research by varying (parameter of the HF concentrations) concentrations of HF (what is HF?) and (the anodization time) time of anodizations. Its structure, as well as its optic, has been characterized. In this research, we did electrical characterization of PS to find its conductivity. The conductivity of PS is important because PS, as a sensor, utilizes the changes of conductivity when it is passed by NO(x=1.2). (The influence of these parameters on I-V characteristics of the PS and on the sensor performances has been studied in detail) The changes of electrical current because of the varying NO concentrations with time were measured using a current measuring system, then plotted. The result (shows) showed that the sensor could detect NO (and NO) gasses ranging from 16 ppb to 200 ppb and NO gas ranging from 12 ppb to 200 ppb, respectively at room temperature (28C) and at adjusted currents ranging from 20 to 800 μA. The result also showed that the sensor was not completely reversible for NO. xxx22ox